PDE9A is expressed in the inner retina and contributes to the normal shape of the photopic ERG waveform - Dhingra, Anuradha; Tummala, Shanti R.; Lyubarsky, Arkady; Vardi, Noga (Frontiers in Molecular Neuroscience, 2014)
The ubiquitous second messenger cGMP is synthesized by guanylyl cyclase and hydrolyzed by phosphodiesterase (PDE). cGMP mediates numerous signaling pathways in multiple tissues. In the retina, cGMP regulates signaling in nearly every cell class including photoreceptors, bipolar cells, amacrine cells, and ganglion cells. In order to understand the specific role of cGMP and its regulating enzymes in different cell types, it is first necessary to localize these components and dissect their influence on the circuits. Here we tested the contribution of PDE9A to retinal processing by recording the electroretinograms (ERG) of PDE9A-/- (KO) mice and by localizing the enzyme. We found that while the scotopic ERG of KO was the same as that of wild type (WT) in both amplitude and kinetics, the photopic ERG was greatly affected. The greatest effect was on the recovery of the b-wave; the falling phase and the b-wave duration were significantly longer in the KO mice for all photopic stimuli (UV, green, or saturating white flashes). The rising phase was slower in KO than in WT for UV and green stimuli. For certain stimuli, amplitudes of both the a- and b-waves were smaller than in WT. Using Lac-Z expression in KO retinas as a reporter for PDE9A expression pattern, we found that PDE9A is localized to GABA-positive and GABA-negative amacrine cells, and likely also to certain types of ganglion cells. Our results indicate that PDE9A, by controlling the level of cGMP, modulates inhibitory processes within the cone pathway. We speculate that these circuits involve NO/cGMP signaling pathways.